Power bi tool applied in financial analysis - Puente Riofrío, Mariana Isabel; Dávalos Mayorga, Eduardo Ramiro; Usca Ordoñez, Erika Paola; Jácome Rovayo, Edgar David (mktDESCUBRE; Vol 1 No 23 (2024): Twenty-third Edition (January - June), 2024)
The ability to analyze and make informed decisions in the case study is limited, because it lacks tools that allow timely visualization of financial information, currently Power BI offers forecasting functions, grouping and quick measures, for this reason the present research aims to apply Power BI as a tool for financial analysis. The research approach was mixed, combining surveys in two contexts to evaluate the impact of the Power BI tool in financial analysis through ANOVA analysis. The results show how the software tool has significantly improved the capability of financial analysis, allowing users of financial information to access relevant data and make informed decisions. It is concluded that Power BI is an essential tool for optimizing financial performance and improving decision making in economic entities.